A wider Trecento
1 online resource (xxxii, 213 pages)
Keywords: Julian Gardner’s preeminent role in British studies of the art of the 13th and 14th centuries, particularly the interaction of papal and theological issues with its production and on either side of the Alps, is celebrated in these studies by his pupils. They discuss Roman works: a Colonna badge in S. Prassede and a remarkably uniform Trinity fresco fragment, as well as monochrome dado painting up to Giotto, Duccio's representations of proskynesis, a Parisian reliquary in Assisi, Riminese painting for the Franciscans, the tomb of a theologian in Vercelli, Bartolomeo and Jacopino da Reggio, the Room of Love at Sabbionara, the cult of Urban V in Bologna after 1376, Altichiero and the cult of St James in Padua, the orb of the Wilton Diptych, and Julian Gardner’s career itself. The contributors to the volume are Serena Romano, Jill Bain, Claudia Bolgia, Louise Bourdua, Joanna Cannon, Roberto Cobianchi, Anne Dunlop, Jill Farquhar, Robert Gibbs, Virginia Glenn, Dillian Gordon, John Osborne and Martina Schilling.